Teaching Vocabulary Learning Strategies to Kurdish EFL University Students - Rezhna Ibrahim Ali; Anjumen Muhammad Sabir; Qismat Muhammad Zahawi (Zanco Journal of Humanity Sciences)
Vocabulary development is a crucial component of learning a foreign language. Hence, teachers’ knowledge of the optimal instructional practices for teaching vocabulary is of prime importance. The aim of the current paper is to (a) examine the effectiveness of teaching vocabulary learning strategies on improving Kurdish EFL students’ vocabulary (b) find out the extent to which teaching vocabulary learning strategies improves students’ vocabulary. To achieve these aims a quasi-experimental design was used. Eighty (80) second year students selected at college of Basic Education/ Salahddin University for the study. The participants took a Vocabulary Level Test (VLT) to measure their vocabulary knowledge and a pre-posttest, which were designed by the researcher depending on the students’ scores in VLT. In this study, the researcher used paired samples t-test to analyze the collected data.  Based on the results, it was found out that there is a significant difference between the students’ outcomes after introducing the VLS. The vocabulary performance level of the experimental group participants increased significantly at the end of the vocabulary training course. However, the control group had a slight improvement in the posttest. These strategies are recommended as reading comprehension and vocabularies teaching techniques based on the findings of the current study.